On the Link Between Global Volcanic Activity and Global Mean Sea Level - Dumont, Stéphanie; Petrosino, Simona; Neves, Maria C. (Frontiers in Earth Science, 2022)
Studying a large number of volcanic eruptions is a way to decipher general characteristics related to volcano dynamics including external forcing whose solid Earth and ocean tides are an example. Many studies have tackled this tidal influence on the onset of volcanic eruptions and more generally, on volcanic activity. However, the interplay between this quasi-permanent forcing and volcanic systems is still poorly understood. With the present study, we propose to consider a global viewpoint to address this interaction. We analyzed the number of monthly volcanic eruptions and the global mean sea-level between 1880 and 2009 using the Singular Spectrum Analysis time-series analysis technique to evaluate the existence of common periodicities. We found multi-decadal components of similar periodicities present in both time-series which lead us to discuss the multiple space and time scales of the tidal forcing that are acting on the worldwide volcanic activity as well as the perspectives of investigating such external processes.